Activity Test of Ethanol Extract of Tamarind Leaves (Tamarindus indica L.) Against the Inhibitory Power of Escherichia coli Bacteria - Khaerul Ihwan; Nurpiah; Dwi Kartika Risfianty; Pahmi Husain; Irna Il Sanuriza; Baiq Naili Dewi Atika; Irfan Jayadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Tamarind leaves (Tamarindus indica L.) contain compounds including saponins, flavonoids, and tannins. The content of tannin compounds in tamarind leaf extract (Tamarindus indica L.) is known to be used as an antidiarrheal bioagent. This study aims to identify antibacterial activity against Escherichia coli bacteria based on the potential of tamarind leaves (Tamarindus indica L.) as an anti-diarrheal bioagent. The design of this research is an experimental laboratory with randomized group design. The samples in this study were divided into 2 control groups, namely negative control (sterile aquades), positive control (ampiciilin), and 3 treatment groups, namely old and young tamarind leaf extract groups with each concentration of 25%, 50%, 75% and 100% with the number of samples for each treatment group as much as 3. Test the effectiveness of antimicrobials using the solid dilution method. The effectiveness of antimicrobials is demonstrated by the large diameter of the inhibitor on Muller Hilton Agar media. The results showed that the inhibitory power of young tamarind leaf extract ranged from 13.8 mm to 14.9 mm, while the inhibitory power of old tamarind leaf extract ranged from 10.7 mm to 11.9 mm, so that the inhibitory power of young tamarind leaf ethanol extract was greater than the type of old tamarind leaf ethanol’s extract.